2021
DOI: 10.1021/acs.jmedchem.1c00624
|View full text |Cite
|
Sign up to set email alerts
|

α/β-Hydrolase Domain (ABHD) Inhibitors as New Potential Therapeutic Options against Lipid-Related Diseases

Abstract: Much of the experimental evidence in the literature has linked altered lipid metabolism to severe diseases such as cancer, obesity, cardiovascular pathologies, diabetes, and neurodegenerative diseases. Therefore, targeting key effectors of the dysregulated lipid metabolism may represent an effective strategy to counteract these pathological conditions. In this context, α/β-hydrolase domain (ABHD) enzymes represent an important and diversified family of proteins, which are involved in the complex environment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 214 publications
(424 reference statements)
0
13
0
Order By: Relevance
“…Phospholipid hydrolases are known to remove one acyl chain from phospholipids, whereas acyltransferase motifs can catalyze the opposite reaction of a phospholipid hydrolase: where a single-chain phospholipid reacts with an acyl-CoA (coenzyme A) to restore a dual-chain phospholipid ( Aguado and Campbell, 1998 ; Eberhardt et al, 1997 ; Lord et al, 2013 ; Zhao et al, 2008 ). The opposing predicted acyltransferase motif in ABHD16A, although biochemically uncharacterized, is present in many integral ER membrane proteins and other ABHD family proteins and has the potential to either add or alter acyl chains to lysophospholipids/phospholipids ( Bononi et al, 2021 ; Harayama et al, 2014 ; Hishikawa et al, 2014 ; Shindou et al, 2013 ; Zhao et al, 2008 ). Lipase-like motifs (GXSXXG) are predicted to have similarity to bacterial lipase motifs (GXSXG), although it is unknown whether ABHD16A’s lipase-like motifs, one near the acyltransferase motif, and one within the alpha/beta hydrolase domain, have lipase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Phospholipid hydrolases are known to remove one acyl chain from phospholipids, whereas acyltransferase motifs can catalyze the opposite reaction of a phospholipid hydrolase: where a single-chain phospholipid reacts with an acyl-CoA (coenzyme A) to restore a dual-chain phospholipid ( Aguado and Campbell, 1998 ; Eberhardt et al, 1997 ; Lord et al, 2013 ; Zhao et al, 2008 ). The opposing predicted acyltransferase motif in ABHD16A, although biochemically uncharacterized, is present in many integral ER membrane proteins and other ABHD family proteins and has the potential to either add or alter acyl chains to lysophospholipids/phospholipids ( Bononi et al, 2021 ; Harayama et al, 2014 ; Hishikawa et al, 2014 ; Shindou et al, 2013 ; Zhao et al, 2008 ). Lipase-like motifs (GXSXXG) are predicted to have similarity to bacterial lipase motifs (GXSXG), although it is unknown whether ABHD16A’s lipase-like motifs, one near the acyltransferase motif, and one within the alpha/beta hydrolase domain, have lipase activity.…”
Section: Resultsmentioning
confidence: 99%
“…[59] For another member of the intracellular lipolytic cascade, HSL, only nonspecific inhibitors could be identified via competitive ABPP, [60] and selective human ATGL inhibition has recently been achieved by NG-497, although via different means of discovery. [61] Many inhibitors of the ABHD protein family are summarized by Bononi et al, [62] several of which have been identified through ABPP. Recently, ABPP enabled the discovery of a new ABHD6 inhibitor that improves selectivity over MGL and FAAH.…”
Section: Competitive Abpp Screening For Lipid Hydrolase Inhibitor Dis...mentioning
confidence: 99%
“…Many inhibitors of the ABHD protein family are summarized by Bononi et al ., [62] several of which have been identified through ABPP. Recently, ABPP enabled the discovery of a new ABHD6 inhibitor that improves selectivity over MGL and FAAH [63] …”
Section: Competitive Abpp Screening For Lipid Hydrolase Inhibitor Dis...mentioning
confidence: 99%
“…These two ABHDs offer new perceptions into Lyso-PS signaling in the cerebellum, the most atrophic brain region in human polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and cataract (PHARC) subjects [ 93 ]. These enzymes can have a potential therapeutic role in the altered lipid metabolism of Lyso-PS in several diseases such as cancer, diabetes, and neurodegenerative diseases [ 94 ].…”
Section: Properties and Functions Of Phospholipids And Lysophospholip...mentioning
confidence: 99%